Pengaruh Media Pembelajaran Kotak Ajaib Dalam Meningkatkan Numerasi Peserta Didik Kelas I Madrasah Ibtidaiyah - Eka Zaqiya Rahmawati; Ria Resti Fauziah; Rahmat Rudianto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of magic box learning media on the numeracy skills of first-grade students at MI Al-Azhar Menganti. This study used a quantitative approach using the true experimental design method and a pretest-posttest control group design. This study was conducted in the experimental and control classes. The results showed that the use of magic boxes was in the "very good" category for use in learning. The effect of using magic boxes applied to the experimental class could improve numeracy skills, as evidenced by the pretest results of students in the experimental and control classes obtaining the highest score of 65 and the lowest score of 39. However, after being given treatment, the posttest results showed that the numeracy skills of students in the experimental class experienced a more significant increase and obtained scores above the KKTP when compared to the control class. The experimental class obtained the highest score of 95 and the lowest 69 in the very high and high categories, while in the control class the highest score was 81 and the lowest 56 in the high and quite high categories. Furthermore, the influence of the magic box media on students' numeracy skills can be seen from the t-table and t-count which show a significance of 5% = 2.086 < 5.374, or 0.000 < 0.05, meaning that the magic box learning media has an effect on improving the numeracy skills of class I students at MI Al-Azhar Menganti.